Organization of Primary Care Practice for Providing Energy Balance Care. Issue 3 (January 2014) - Klabunde, Carrie N.; Clauser, Steven B.; Liu, Benmei; Pronk, Nicolaas P.; Ballard-Barbash, Rachel; Huang, Terry T.-K.; Smith, Ashley Wilder
Purpose: Primary care physicians (PCPs) may not adequately counsel or monitor patients regarding diet, physical activity, and weight control (i.e., provide energy balance care). We assessed the organization of PCPs' practices for providing this care. Design: The study design was a nationally representative survey conducted in 2008. Setting: The study setting was U.S. primary care practices. Subjects: A total of 1740 PCPs completed two sequential questionnaires (response rate, 55.5%). Measures: The study measured PCPs' reports of practice resources, and the frequency of body mass index assessment, counseling, referral for further evaluation/management, and monitoring of patients for energy balance care. Analysis: Descriptive statistics and logistic regression modeling were used. Results: More than 80% of PCPs reported having information resources on diet, physical activity, or weight control available in waiting/exam rooms, but fewer billed (45%), used reminder systems (< 30%), or received incentive payments (3%) for energy balance care. A total of 26% reported regularly assessing body mass index and always/often providing counseling as well as tracking patients for progress related to energy balance. In multivariate analyses, PCPs in practices with full electronic health records or those that bill for energy balance care provided this care more often and more comprehensively. There were strong specialty differences, with pediatricians more likely (odds ratio, 1.78; 95% confidence interval, 1.26–2.51) and obstetrician/gynecologists less likely (odds ratio, 0.28; 95% confidence interval, 0.17–0.44) than others to provide energy balance care. Conclusion: PCPs' practices are not well organized for providing energy balance care. Further research is needed to understand PCP care-related specialty differences.